Optimum extraction condition of Anacardium occidentale on antiurolithiatic activities (in-vitro) - Nur Fazira Abdul Rahim,; Norhayati Muhammad,; Norazlin Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Urolithiasis or kidney stone has become a worldwide problem including Malaysia. Its management is depending on surgical procedures that are quite costly and can cause reoccurrence. Anacardium occidentale (cashew) has been used traditionally to treat urolithiasis but no scientific data has been recorded that proven its efficiency particularly on its extraction parameters. Therefore, this study aims to identify the optimum extraction parameters of A. occidentale leaves extracts on in-vitro antiurolithiatic activities using Response Surface Methodology (RSM). The effect of three extraction parameters (solvent concentration, X1; extraction temperature, X2; extraction time, X3) on antiurolithiatic activities (turbidity or nucleation assay, Y1; titrimetric or calcium oxalate dissolution assay, Y2) were determined by Central Composite Design (CCD). The results showed that each parameter and its interaction significantly affect the antiurolithiatic activities (p < 0.05). The quadratic model was closely fitted for all responses as the R2 values obtained were 0.9786 (turbidity assay) and 0.9956 (titrimetric assay). The optimum extraction condition of A. occidentale leaves extract suggested by the predicted model was at 0.4% ethanol concentration, temperature 31.5 ℃ and for 30 min of extraction time, exhibited antiurolithiatic activities of 85.57 ± 0.43% (turbidity) and 96.48 ± 0.70% (titrimetric). The phytochemical screening was done on the presence of phenols, tannins, flavonoids, alkaloids, saponins as well as terpernoids and all phytochemicals were identified in the optimized A. occidentale leaves extract. This study has given basic scientific evidence that optimum extraction conditions are necessary to obtain optimum antiurolithiatic activity.